Analysis of the Effect of Compensation, Motivation, and Job Satisfaction to Employee Perfromance: Case Study at Customer Interaction Division of PT XYZ - SB Diah Pudjiastuti; Rosdiana Sijabat (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The purposes of this study are to analyze the positive effect of compensation and motivation on job satisfaction, the positive affect of compensation and motivation to employee performance, the positive affect of job satisfaction to employee performance, the role of job satisfaction as mediation between compensation to employee performance and motivation to employee performance. Number of samples taken was 154 respondents with method nonprobability samping – convenience samping technique. Data was collected by distributing questionnaires to measure 17 questions using a 5 points likert scale to the employee of internet provider. The data will be analyzed using SmartPls and the technique used is hipotesis testing. The result that compensation and motivation has positive and significant affect to job satisfaction, compensation doesn’t affect to employee performance, job satisfaction has positive and significant affect to employee performance, job satisfaction as full mediation between compensation to employee performance and job satisfaction as partial mediation between motivation to employee performance. The results of this study can provide input to company management to determine job satisfaction factor of employee so it will improve employee performance.